Tutorial pembuatan media komik digital pada pembelajaran IPA kelas 4 - Rizky, Iftitah A’immatur (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to prove the effectiveness of digital comic media used in science learning for grade 4 elementary schools. With a monotonous teacher background in using conventional learning without media so that students' interest in participating in learning is reduced. The method used is descriptive quantitative. The sampling technique used is purposive sampling. The research subjects were 60 students from the two classes taken for the study, namely the control class with 30 students and the experimental class with 30 students. The instruments used in this study were tests and observation sheets. The results showed that the use of digital comics media, especially for science learning, was effective as evidenced by an increase in student learning outcomes, especially the material for plant parts and their functions.